2017
DOI: 10.1002/chem.201704110
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Assembly of Phosphole Oxide Based Alkynylplatinum(II) 2,6‐Bis(N‐alkylbenzimidazol‐2’‐yl)pyridine Complexes—An Interplay of Hydrophobicity and Aromatic π‐Surfaces

Abstract: A new class of phosphole oxide based alkynylplatinum(II) 2,6-bis(N-alkylbenzimidazol-2'-yl)pyridine (bzimpy) complexes were synthesized and characterized. Their self-assembly was driven by hydrophobic-hydrophobic and π-π stacking interactions. The self-assembly properties were also investigated by UV/Vis absorption spectroscopy, which revealed that the alkyl-chain length of the bzimpy moiety and the π-surface area of the alkynyl ligand have significant influence on the overall self-assembly process. The alkyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 151 publications
0
8
0
Order By: Relevance
“…Prototypical and some interesting applications include luminescent sensors, photochromism, supramolecular assemblies, and organic electronics. , The attractiveness of phosphole oxide-containing systems originates from their rich photophysical properties, diverse structural functionalization opportunities as well as unprecedented electronic properties induced by the σ–π hyperconjugation . In addition, the electron-withdrawing PO unit on the phosphole oxide moiety is well-received as an effective group in improving the electron transport of the active materials. , Also, with the tetrahedral geometry adopted by the phosphorus center, the excessive intermolecular π-stacking of the molecules can be prevented, which is advantageous for achieving uniform thin films. These favorable features offered by phosphole oxides are highly beneficial for the preparation of solution-processable molecular materials for organic resistive memories. Very recently, introduction of a benzophosphole oxide moiety into a cyclometalated alkynylgold­(III) complex has been demonstrated to realize a ternary organic resistive memory .…”
mentioning
confidence: 99%
“…Prototypical and some interesting applications include luminescent sensors, photochromism, supramolecular assemblies, and organic electronics. , The attractiveness of phosphole oxide-containing systems originates from their rich photophysical properties, diverse structural functionalization opportunities as well as unprecedented electronic properties induced by the σ–π hyperconjugation . In addition, the electron-withdrawing PO unit on the phosphole oxide moiety is well-received as an effective group in improving the electron transport of the active materials. , Also, with the tetrahedral geometry adopted by the phosphorus center, the excessive intermolecular π-stacking of the molecules can be prevented, which is advantageous for achieving uniform thin films. These favorable features offered by phosphole oxides are highly beneficial for the preparation of solution-processable molecular materials for organic resistive memories. Very recently, introduction of a benzophosphole oxide moiety into a cyclometalated alkynylgold­(III) complex has been demonstrated to realize a ternary organic resistive memory .…”
mentioning
confidence: 99%
“…Consequently, it is frequently observed that aggregates of these complexes dissolve when studied at low concentrations . In contrast, aggregation of Pt II complexes is promoted in solution due to their square-planar geometry, π–π and hydrophobic interactions of the ligands, as well as by Pt–Pt interactions at short distances (<3.5 Å). , These features make Pt II complexes very sensitive toward microenvironmental changes, and the formation of supramolecular Pt II assemblies can be induced in a controlled fashion in the presence of ordered counter-anions. This can also alter the photophysics of the complexes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, phosphole, being an organic molecular compound or as a ligand for coordination to various transition metal centers, has received increasing research interests in the past decade 14,44–60 . Desirable properties, such as tunable electrochemical characteristics, facile molecular functionalization and intermolecular packing have been observed in various classes of phosphole moieties, allowing the design of smart materials in the fields of organic electronics, 14,52,59,60 photochromism, 44,54 chemosensing, 50,51,56 and supramolecular chemistry 48,53,55,57 .…”
Section: Introductionmentioning
confidence: 99%